Forced displacement : why rights matter - Grabska, Katarzyna; Mehta, Lyla (Palgrave Macmillan, 2008)
Uprootedness, exile and forced displacement, be they due to conflict, persecution or so-called 'development', are conditions which characterise the lives of millions across the globe. This book analyses a range of displacement situations, including development 'oustees', refugees and internally displaced persons.